Answer:
The roots are
![x=-1+i(√(10))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7i3ul417vn3r3yr2qvw8y2yk0ybaoeyfjj.png)
![x=-1-i(√(10))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mncfxvxem52a6khjhazga17jcfd0gn2xu3.png)
Explanation:
we have
![2x^2+4x+7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5i4cxhb1i6knesz6a2sb3qok5qdrv4pfbg.png)
To find the roots equate the equation to zero
so
![2x^2+4x+7=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vqg7a8uvostmztp9p9a2ovjayl1zrvpmzs.png)
we know that
The formula to solve a quadratic equation of the form
is equal to
![x=\frac{-b\pm\sqrt{b^(2)-4ac}} {2a}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v8sisz55e1m1m05f4zv1qh4p0v753i9v3w.png)
in this problem we have
![2x^2+4x+7=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vqg7a8uvostmztp9p9a2ovjayl1zrvpmzs.png)
so
![a=2\\b=4\\c=7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/di55a7t5dbmq08wss06fdnywhtx7caaf85.png)
substitute in the formula
![x=\frac{-4\pm\sqrt{4^(2)-4(2)(7)}} {2(2)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7qoqywv88jp6gs2ryz2l5urewdgtlluofa.png)
![x=\frac{-4\pm√(-40)} {4}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/sqorafzrkdeu4rapggsrcs4agg8jqmzc0c.png)
Remember that
![i=√(-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tjbsl17yeu7kf8jfbjdj2ptl3waguz07at.png)
so
![x=\frac{-4\pmi√(40)} {4}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/f5oubgr9pnjddhwkkq4ozxibyblobvahay.png)
![x=\frac{-4\pm2i√(10)} {4}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vy0alkxj9xv7oq6qwy4j3ebpmnwnoo0ow1.png)
simplify
![x=\frac{-2\pm i√(10)} {2}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/o9rw9y1xytibwfxhbyqquryevw4a04dnvr.png)
therefore
The roots are
![x=\frac{-2+i√(10)} {2}=-1+i(√(10))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/c710i1ld9n4o7ookev5pd4p0tygk5k3pe1.png)
![x=\frac{-2-i√(10)} {2}=-1-i(√(10))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iy409p38cyv187s4itacdakof70go0zwsn.png)